The molecular biology of the inositol trisphosphate receptor - Patterson, Randen (Henry Stewart Talks, 2007)
Activation of the IP3-receptor (IP3R), a major endoplasmic Calcium release channel in many cells, is activated by the second messenger inositol 1,4,5-trisphosphate (IP3), The IP3R is unique in that it can integrate signals from numerous cellular pathways via a myriad of inputs which include nucleotide binding, phosphorylation, Calcium binding and protein-protein interactions, A diverse range of cellular functions are modulated by the IP3R including contraction/excitation, secretion, gene expression, cell cycle, apoptosis and cellular growth, The nodal properties of the IP3R and the mechanisms by which this occurs
Archived at 2021/02/25